Multivessel Percutaneous Coronary Intervention in Patients with Acute ST-segment Elevation Myocardial Infarction in Same Sitting - Islam, AHM Waliul; Munwar, Shams; Bhuiyan, Azfar H; Talukder, Sahabuddin; Reza, AQM; Ahmed, Tamzeed; Islam, Nighat; Siddique, Atique Bin; Yousuf, Intekhab; Shohel, Shaifur Rahman; Tanvir, Sarder Md; Karim, Aparajita; et al. (Cardiovascular Journal, 2015)
Background: Aim of the study was to evaluate the primary procedural success of Multivessel Percutaneous coronary intervention in patients with acute ST-segment elevated myocardial infarction at the same sitting. Methods: Total 23 (13.4%) patients were enrolled in this very preliminary study, among the total 171 patients who had primary PCI at our center from Jan 2010 to February 2015. Among them, Male: 20 and Female: 3. Total 52 stents were deployed in 46 territories. Mean age were for both male and female were 54 yrs. Associated coronary artery disease risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, positive family history for coronary artery disease and Smoking. Results: Among the study group; 17(74%) were Dyslipidemic, 11(47.8%) were hypertensive; 8(34.8%) patients were Diabetic, positive family history 4(17.4%) and 9(39%) were all male smoker. Female patients were more obese (BMI: M 26: F 27). Common diagnosis at admission based on ECG evidence was; Inferior wall myocardial infarction: 12 (52.2%), Anterior wall myocardial infarction 9(39.1%) and lateral 2(8.7%). Common stented territory was left anterior descending artery 9(39.1%), right coronary artery 7(30.4%), and left circumflex artery 7(30.4%). Stent used: Bare metal stent 3 (5.7%), DES: 49 (94.2%). Among the different drug eluting stents, Everolimus 26 (52%), Sirolimus 8(15.4%) and Zotarolimus 9(17.3%), Paclitaxel 2 (3.8%), Biolimus 2 (3.8%), Genous 2 (3.8%). Conclusion: In the current prospective non randomized study, we found that the multivessel primary PCI for ST elevation myocardial infarction with non-culprit vessel are suitable for PCI at the same sitting with better in-hospital and 1 yr survival outcome. Cardiovasc. j. 2015; 8(1): 53-58